Estimation of Random Utility Models in R: The mlogit Package - Croissant, Yves (Journal of Statistical Software, 2020)
mlogit is a package for R which enables the estimation of random utility models with choice situation and/or alternative specific variables. The main extensions of the basic multinomial model (heteroscedastic, nested and random parameter models) are implemented.